STRATEGI PROGRAM PELATIHAN BAGI PENYANDANG DISABILITAS TUNARUNGU DI KOPI TULI TEBET JAKARTA SELATAN - Atiyah Faridah Hanan; Irhamni Rahman (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study analyzes the empowerment strategies for individuals with hearing disabilities at Kopi Tuli through a barista training program that emphasizes technical skills, self-confidence, visual communication, and social integration. Using a qualitative case study approach, data were collected through interviews and observations involving the owners, Deaf baristas, and customers. The findings indicate that Kopi Tuli functions both as an inclusive workplace and as a public educational space on Deaf culture. The challenges identified include limited trainers, restricted access to advanced training, and low public understanding. Overall, this inclusivity-based strategy effectively supports the independence of Deaf individuals and serves as an example of sociopreneurship practice in Indonesia.